Validation and Clinical Application of a Biopsychosocial Model of Pain Intensity and Functional Disability in Patients with a Pediatric Chronic Pain Condition Referred to a Subspecialty Clinic. (22nd October 2013) - Vetter, Thomas R.; McGwin, Gerald; Bridgewater, Cynthia L.; Madan-Swain, Avi; Ascherman, Lee I.
Abstract : Background . Pediatric chronic pain is considered to be a multidimensional construct that includes biological, psychological, and social components. Methods . The 99 enrolled study patients (mean age 13.2 years, 71% female, 81% Caucasian) and an accompanying parent completed a series of health-related questionnaires at the time of their initial appointment in a pediatric chronic pain medicine clinic. Results . Significant correlations (r ≥ 0.30, P < 0.05 ) were observed between pediatric chronic pain intensity and patient anxiety, patient depression, patient pain coping, parent chronic pain intensity, and parent functional disability. Pediatric chronic pain intensity was significantly associated with patient anxiety (P = 0.002 ). Significant correlations (r ≥ 0.30, P < 0.05 ) were observed between pediatric functional disability and patient chronic pain intensity, patient anxiety, patient depression, patient pain coping, parent chronic pain intensity, parent functional disability, parent anxiety, parent depression, and parent stress. Pediatric functional disability was significantly associated with patient chronic pain intensity (P = 0.025 ), patient anxiety (P = 0.021 ), patient pain coping (P = 0.009 ), and parent functional disability (P = 0.027 ). Conclusions . These findings provide empirical support of a multidimensional Biobehavioral Model of Pediatric Pain. However, the practical clinical application of the present findings and much of the similar previously published data may be tenuous.